MACROSCOPIC, MICROSCOPIC AND BIO-CHEMICAL CHARACTERISTICS OF FRESH DOG SEMEN - KURIEN, M O; KATHIRESAN, D; SELVARAJU, M; PATTABIRAMAN, S R (The Indian Journal of Animal Reproduction, 2023)
Forty semen ejaculates obtained from 10 healthy adult mongrel dogs by digital manipulation technique were examined to assess the macroscopic, microscopic and biochemical characteristics. In the sperm rich fraction, the volume (0.9 to 1.5 ml), colour (white to milky white), consistency of semen (thin to medium), overall mean sperm concentration (319.00 + 11.79 million per ml), pH (5.80 to 6.70), initial sperm motility (80 to 90 per cent), live spermatozoa (74 to 91 per cent), abnormal spermatozoa (7 to 10 per cent), intact acrosome (88 to 96 per cent) and hypo-osmotic swelling response (73 to 96 per cent) were recorded. The aspartate aminotransferase enzyme leakage into the seminal plasma ranged from 36 to 48 units per ml. The mean level of the aspartate aminotransferase recorded was 40.00 +1.11 units per ml of seminal plasma in dog semen.